2020
DOI: 10.22515/sustinere.jes.v4i2.118
|View full text |Cite
|
Sign up to set email alerts
|

Household food security during Covid-19 pandemic in Daerah Istimewa Yogyakarta, Indonesia

Abstract: Household food security in Indonesia depends on many factors. This study aims to describe household food security during the Covid-19 pandemic in Daerah Istimewa Yogyakarta (DIY). This research was conducted using a questionnaire for taking data. This study showed that there was a difference in household food security between the pre-pandemic of Covid-19 and during the pandemic of Covid-19. The hunger scale di DIY at the pre-pandemic of Covid-19 was 6% and increased during the pandemic of Covid-19 to 11%. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
2
7
0
2
Order By: Relevance
“…The results of the McNamar test analysis stated that the husband's and wife's occupation and the number of workers in the household before and during the pandemic were significantly different. This study is in line with research in Yogyakarta which stated that there was an increase in the number of unemployment between before and during the pandemic from 17.2% to 22.1% 39 . Research in Austin, Texas showed that 46% of families experienced a job loss, disruption or reduction 40 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the McNamar test analysis stated that the husband's and wife's occupation and the number of workers in the household before and during the pandemic were significantly different. This study is in line with research in Yogyakarta which stated that there was an increase in the number of unemployment between before and during the pandemic from 17.2% to 22.1% 39 . Research in Austin, Texas showed that 46% of families experienced a job loss, disruption or reduction 40 .…”
Section: Resultssupporting
confidence: 92%
“…Households with income < minimum salary wage experienced an increase from 61.4% before pandemic to 71.8% during pandemic. This result is in line with a study in Yogyakarta which stated that households with a monthly income of < IDR 1,000,000.00 increased from 6.6% to 13.1% since the COVID-19 pandemic 39 . In Nigeria, there were 47.9% of respondents who experienced a decrease in income and 8.4% of respondents who did not have any income during COVID-19 pandemic 41 .…”
Section: Resultssupporting
confidence: 90%
“…Ketahanan pangan didefinisikan sebagai suatu kondisi ketersediaan pangan yang cukup bagi setiap orang pada setiap saat dan setiap individu yang mempunyai akses untuk memperolehnya, baik secara fisik maupun ekonomi (Purnasari et al, 2020). Fokus ketahanan pangan tidak hanya pada penyediaan pangan tingkat wilayah tetapi juga ketersediaan dan konsumsi pangan tingkat daerah dan rumah tangga, dan bahkan bagi individu dalam memenuhi kebutuhan gizinya.…”
Section: Pendahuluanunclassified
“…Food safety refers to handling, processing, and how the conditions and practices of food storage from producers to consumers are aimed at ensuring consumer safety from food-borne diseases (FBD) outbreaks caused by unsafe food [8]. Consumer awareness regarding food safety has the main challenge of misuse of prohibited additives for food and use exceeding the maximum limit.…”
Section: Resultsmentioning
confidence: 99%